The Commonly Encountered Bacterial Agents and their Antibiotic Sensitivity in the Neonatal Intensive Care Units of Cairo University Children Hospitals: An Observational Study - Dina Khedr; Peter Samaan; Abdulrahman Abdulrazek; Noha Adel Yassin (Pediatric Sciences Journal)
Background: The emergence of multidrug-resistant organisms (MDROs) endangered neonates in the neonatal intensive care units (NICUs). Aim of the work: To identify the most common bacterial agents and MDROs in neonatal sepsis in our center, their antibiotic sensitivity, the possible associated neonatal and maternal risk factors, and their relation to the outcome. Subjects and Methods: This retrospective study included 138 neonates with culture-proven sepsis (blood, endotracheal tube aspirates (ETA), urine, cerebrospinal fluid (CSF), or wound swabs) admitted in 1 year (2022). Data was obtained from the patient's files, including various clinical and laboratory characteristics and risk factors and outcomes. Results: This study included 138 newborns with confirmed neonatal sepsis. Of all cultures performed, multidrug resistant (MDR) Klebsiella pneumoniae was the most frequently isolated organism among 37 (27%) cases, that was mostly sensitive to polymyxin B was, followed by coagulase-negative Staphylococcal aureus (CoNS) in 32 cases, which was the most sensitive to vancomycin. Of all performed cultures, 71(51%) revealed MDROs (MDR Klebsiella pneumoniae, MRSA, MDR Acinetobacter, MDR Enterobacter, and MDR E. coli). The frequency of MRSA and MDR Klebsiella pneumoniae in the blood cultures was higher among those who died than those who survived (p= 0.03) and (p= 0.04) respectively. Logistic regression showed that bulging fontanel, feeding intolerance, temperature instability, long duration of admission, and high CRP were associated with high mortality among the studied cases (odd ratio > 1 (p= 0.0001), (p=0.007), (p=0.03), (p=0.001) and (p=0.006) respectively, while normal blood pressure, blood transfusion, appropriate birth weight, and normal serum albumin were protective variables (odd ratio < 1) (p= 0.008), (p=0.03), (p=0.001) and (p=0.001) respectively. Conclusion: MDROs were isolated in more than 50% of neonatal sepsis. The methicillin- resistant Staphylococcus aureus and MDR Klebsiella pneumoniae in blood cultures were associated with higher mortality in neonatal sepsis.